2019
DOI: 10.1103/physrevb.100.155144
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and transport properties in the magnetic topological insulators MnBi2Te4(Bi2<

Abstract: The observation of quantized anomalous Hall conductance in the forced ferromagnetic state of MnBi2Te4 thin flakes has attracted much attentions. However, strong magnetic field is needed to fully polarize the magnetic moments due to the large antiferromagnetic interlayer exchange coupling. Here, we reported the magnetic and electrical transport properties of the magnetic van der Waals MnBi2Te4(Bi2Te3)n (n=1,2) single crystals, in which the interlayer antiferromagnetic exchange coupling is greatly suppressed wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 36 publications
7
55
0
1
Order By: Relevance
“…Recently, it was predicted that this physics can be realized in MnBi 2 Te 4 [14,15]. Subsequently, single crystals of MnBi 2n Te 3n+1 were grown and physical properties, including electrical and thermal transport, magnetization, neutron scattering, etc., were measured which support possible realization of the axion insulator in these materials [16][17][18][19][20][21]. While some ARPES studies reported observation of a gapped surface state in MnBi 2n Te 3n+1 and thus possible axion insulator behavior [22][23][24][25], many others showed evidence that the surface state in this material remains gapless or diminished gap down to low temperatures [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 78%
“…Recently, it was predicted that this physics can be realized in MnBi 2 Te 4 [14,15]. Subsequently, single crystals of MnBi 2n Te 3n+1 were grown and physical properties, including electrical and thermal transport, magnetization, neutron scattering, etc., were measured which support possible realization of the axion insulator in these materials [16][17][18][19][20][21]. While some ARPES studies reported observation of a gapped surface state in MnBi 2n Te 3n+1 and thus possible axion insulator behavior [22][23][24][25], many others showed evidence that the surface state in this material remains gapless or diminished gap down to low temperatures [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 78%
“…were grown via a solid-state reaction method as described in an earlier study [5,40]. X-ray diffraction measurements were carried out on each sample to identify the correct phase.…”
Section: Sample Preparation and Characterization Single Crystals Of mentioning
confidence: 99%
“…MnBi 2 Te 4 (n = 0) and MnBi 4 Te 7 (n = 1) show typical A-type antiferromagnetism (AFM), with the interlayer antiferromagnetic interaction being weaker than the stronger interlayer ferromagnetic (FM) interaction. 150,151 If the interval thickness continues to increase, the interlayer exchange coupling will be further weakened. Magnetization tests and theoretical calculations show that magnetospheric decouples from n = 2 and 3.…”
Section: Antiferromagnetismmentioning
confidence: 99%